-3(3x-27)=5x+29

Simple and best practice solution for -3(3x-27)=5x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3x-27)=5x+29 equation:


Simplifying
-3(3x + -27) = 5x + 29

Reorder the terms:
-3(-27 + 3x) = 5x + 29
(-27 * -3 + 3x * -3) = 5x + 29
(81 + -9x) = 5x + 29

Reorder the terms:
81 + -9x = 29 + 5x

Solving
81 + -9x = 29 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
81 + -9x + -5x = 29 + 5x + -5x

Combine like terms: -9x + -5x = -14x
81 + -14x = 29 + 5x + -5x

Combine like terms: 5x + -5x = 0
81 + -14x = 29 + 0
81 + -14x = 29

Add '-81' to each side of the equation.
81 + -81 + -14x = 29 + -81

Combine like terms: 81 + -81 = 0
0 + -14x = 29 + -81
-14x = 29 + -81

Combine like terms: 29 + -81 = -52
-14x = -52

Divide each side by '-14'.
x = 3.714285714

Simplifying
x = 3.714285714

See similar equations:

| (x^2)+2=0 | | 3x=87+x | | 4x+20=50-10 | | 33=6x+3x-x+9 | | 4x+4+2x=3x+1 | | X^2-3x+36=0 | | -3=6y+9-4y | | ln(x)+ln(x-3e)=ln(4)+2 | | 59=4k-7+3+5k | | 2x^2+4x+60=0 | | 7-4(-x+3)=2x | | -10g^2+13g=4 | | 14=9+3y-2y | | -6g^2+9g+8=0 | | 4(v-4)-6v=-8 | | 3(10)+5(x)=75 | | 5(3x+1)-2(5x+35)=0 | | 3(-4)-2(-2*3)+9= | | -4(v-2)=-4(v-8)+8v | | -(x-2)=2-x | | 6+5m-4=9m+20-6m | | 3x+2x=54 | | -0.9x+2.65=-0.5x+5.45 | | 15+5n=6n | | 5x-20=15y+60 | | 2x-5=6x+4 | | 2y^2+17y+35= | | -4x+3=7x-8 | | 3x+8.13=2x | | 9x^2+60x=-100 | | 2x^2-4x+100=100 | | 15-5(1-1)=120-5 |

Equations solver categories